2012
DOI: 10.1590/s0102-09352012000400033
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da qualidade da casca dos ovos provenientes de matrizes pesadas com diferentes idades

Abstract: RESUMOFoi realizado um estudo sobre qualidade da casca dos ovos incubáveis provenientes de matrizes pesadas com diferentes idades, por meio da avaliação da relação entre peso da casca e peso do ovo e análises de peso específico, espessura, porosidade, resistência e microscopia eletrônica. Os dois tratamentos foram definidos pela idade da matriz, sendo considerados ovos de matrizes novas  33 semanas  e de matrizes velhas  63 semanas. Os ovos de matrizes com 33 semanas foram mais leves, e o número de poros po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
13
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 18 publications
6
13
0
5
Order By: Relevance
“…Eggs from laying hens aged 62 and 51 weeks show larger weight than the ones from hens aged 39 and 21, respectively. This data agrees with findings by Barbosa et al (2012) and Trindade et al (2007), which reported larger EWs as the bird aged. According to Almeida et al (2006), this is due to the production of larger ovarian follicles, which determine the production of eggs with large yolks, thereby increasing the ratio of yolk weight and egg weight.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Eggs from laying hens aged 62 and 51 weeks show larger weight than the ones from hens aged 39 and 21, respectively. This data agrees with findings by Barbosa et al (2012) and Trindade et al (2007), which reported larger EWs as the bird aged. According to Almeida et al (2006), this is due to the production of larger ovarian follicles, which determine the production of eggs with large yolks, thereby increasing the ratio of yolk weight and egg weight.…”
Section: Resultssupporting
confidence: 93%
“…Table 2, the bird's age influenced significantly (P≤0.05) the number of pores in the shell (NP), with older birds showing higher NP by cm 2 than younger ones. Similar data have been found in the studies of Barbosa et al (2012). Pore size, however, suffered no influence (P>0.05) from bird's age (Table 3).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations